2021
DOI: 10.4235/agmr.20.0095
|View full text |Cite
|
Sign up to set email alerts
|

Association of the FRAIL Scale with Geriatric Syndromes and Health-Related Outcomes in Korean Older Adults

Abstract: BackgroundNeeds exist for appropriate tools for frailty screening in community-dwelling older people, with growing older population. We aimed to investigate the association of geriatric conditions and healthrelated outcomes with the 5-item FRAIL scale in a Korean rural community setting. MethodsComprehensive geriatric assessments including FRAIL scale were performed in 1,292 communitydwelling people (mean age: 74.6 years) in the Aging Study of Pyeongchang Rural Area (ASPRA). These population was prospectively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…In addition to six studies [38][39][40][41][42][43] that only enrolled male or female individuals, the other studies all consisted of both sexes. Almost all the identified studies provided corresponding HRs for the risk of death, with potential adjustment factors including age and sex, but three studies [25,44,45] reported the OR.…”
Section: Study Characteristics and Quality Assessmentmentioning
confidence: 99%
“…In addition to six studies [38][39][40][41][42][43] that only enrolled male or female individuals, the other studies all consisted of both sexes. Almost all the identified studies provided corresponding HRs for the risk of death, with potential adjustment factors including age and sex, but three studies [25,44,45] reported the OR.…”
Section: Study Characteristics and Quality Assessmentmentioning
confidence: 99%
“…We used the FRAIL and MMSE-K scales to assess level of frailty and cognitive function. Although the instruments for measuring frailty and cognitive function were consistent with previous research on older populations ( 2 , 26 , 36 , 51 , 52 ), we cannot rule out the possibility that the prevalence of cognitive frailty could vary if different measures are used. Moreover, we did not consider a broad spectrum of social activities or specific cognitive domains.…”
Section: Discussionmentioning
confidence: 70%
“…The simple FRAIL questionnaire was not inferior to the Kihon + 3 index 23 ) and was associated with geriatric syndromes and 3-year health-related outcomes, such as disability, institutionalization, and mortality. 24 ) The results of our analysis showed that the FRAIL scale, a phenotype-based questionnaire, behaved similarly in general to a deficit accumulation model-based Kihon + 3 index. Based on these findings, subsequent studies to identify a core aging phenotype underlying the broad definitions of frailty were conceptualized.…”
Section: Findings and Implicationsmentioning
confidence: 60%